ChemInform Abstract: Doping Effects of Group‐IIIA Elements on Physical Properties of ZnMgXO (X: Al, Ga, In, Tl) Transparent Conducting Oxide Films Prepared by RF Magnetron Sputtering. Issue 48 (2nd December 2014) - Jeong, Sang‐Hun; Park, Jang‐Ho; Lee, Byung‐Teak
Abstract Zn0.88Mg0.1M0.02O (M: Al, Ga, In, Tl) films are grown on quartz by radio‐frequency magnetron sputtering using ceramic targets prepared by cold isostatic pressing and sintering of the respective metal oxide powders (950 °C, 6 h).